Synthesis of 4-Arylaminoquinazolines from 2-amino-N'-Arylbenzamidines and Orthoesters via the Dimroth Rearrangement of Intermediate Quinazolin-4(3H)- Imines - Zemlak, Krzysztof; Szczepankiewicz, Wojciech; Kula, Bartłomiej; Bieg, Tadeusz (Current Organic Chemistry, 2018)
A reaction of 2-amino-N'-arylbenzamidines with triethyl orthoformate, orthoacetate and orthopropionate leads to quinazolin-4(3H)- imines. These compounds transform to 4-arylaminoquinazolines by heating in acetic acid according to the Dimroth rearrangement mechanism. Unexpectedly, these imines heated in ethanol gave mixtures of 4-arylaminoquinazolines and 4- ethoxy-quinazoline.
Keywords: orthoformate